A systematic review and meta-analysis of the relationship between subjective interoception and alexithymia: Implications for construct definitions and measurement. - Kristen Van Bael; Jessica Scarfo; Emra Suleyman; Jessica Katherveloo; Natasha Grimble; Michelle Ball (PLoS ONE)
Although research indicates that self-reported interoception is associated with deficits in identifying and describing emotional experience, and externally oriented thinking styles (alexithymia), this relationship appears moderated by how interoception is measured. A systematic review and meta-analyses examined the association between self-reported interoception and alexithymia, investigating how different interoceptive questionnaires relate to alexithymia at global and facet levels. PsychINFO, PubMed, Scopus, and Web of Science databases were searched with predefined terms related to self-reported interoception and alexithymia. Three reviewers independently assessed articles, extracted data, and undertook risk of bias assessment. Thirty-two cross-sectional studies published between 1996 and 2023 were included. Random-effects meta-analyses and narrative synthesis indicated that global alexithymia was positively associated with measures of interoceptive confusion, autonomic nervous system reactivity, and heightened interoceptive attention, and inversely associated with interoceptive accuracy and adaptive interoception, indexed by composite Multidimensional Assessment of Interoceptive Awareness scores, but particularly interoceptive trusting, self-regulation, and attention regulation. These patterns were observed for alexithymic facets and stronger in magnitude for difficulty identifying feelings and difficulty describing feelings, relative to externally oriented thinking. Overall, results suggested that the association between self-reported interoception and alexithymia differs as a function of the interoceptive self-report. The review highlighted issues with construct definition and operationalisation and determined that existing interoceptive self-reports broadly capture maladaptive and adaptive sensing, attention, interpretation, and memory. The findings underscore the importance of specifying interoceptive constructs and using appropriate assessments to improve convergence between constructs and measurements, further suggesting potential clinical utility in using existing self-reports to measure interoception and alexithymia, facilitating interventions targeting mind-body connections.